PERAN PERBANKAN DALAM IMPLEMENTASI BISNIS HIJAU DAN PEMBANGUNAN BERKELANJUTAN - Sari Yuniarti (Jurnal Keuangan dan Perbankan, 2013)
Nowadays green business was the solution offered by industry agents in saving earth in which they were demanded to have active role in environment management, even with the increase of industry aware on the importance of environment management, they were proactive in the effort to manage pollution to produce safe and hospitable environment product. This greening movement also happened in banking with the terminology green banking. Green banking could mean as banking that in doing the business was based on sustainability development principle, especially in credit or funding, namely there was ecology balance, human welfare, and also the development of social cultural in society. Bank Indonesia hoped that green banking would give positive contribution on the effort of fiscal and monetary policy strength that some of them were reflected from the decline of oil import charge and agriculture product because there was increase in supply of domestic energy from the reformed energy sources, the increase of the energy use efficiency by industry, and the increase of organic agricultural product supported by national banking.